Evaluation of effectiveness parameters on gas dehydration plant (simulation) - Fong Ling, Tan (2014)
The transportation of natural gas through pipeline is an important aspect in the world. However the combination of hydrocarbon and water under suitable condition form hydrates in pipeline. These hydrates will cause blockage of pipeline. Gas dehydration is the method used to remove water from the hydrocarbon for the smooth transfer of natural gas in pipeline around the world. This research describes the effectiveness parameters on gas dehydration plant. The parameters studies are gas flow rate, absorber pressure and number of equilibrium stages of an absorber in liquid triethylene glycol (TEG) dehydration units. ASPEN HYSYS is used for steady state simulation, design, performance monitoring and optimization of oil and gas production, gas processing and petroleum refining industries. Peng-Robinson equation of state and MESH equation are chosen in the system. In conclusion, the results showed that increasing gas flow rate decreases the dehydration efficiency. While, dehydration efficiency decreases with increasing of operating pressure. Increasing of equilibrium stages increases the dehydration efficiency